The market premium for the option to close: evidence from Australian gold mining firms. (21st December 2015) - Kelly, Simone
Abstract: This study shows the market value of gold mining firms contains a premium for the option to close. The sample uses 41 gold mining producers listed on the Australian Stock Exchange from 1987 to 2013. The premium of the market price over the present value of cash flows is isolated and a pooled cross‐sectional regression tests the degree of association between that premium and theoretical option premiums. The results show market prices incorporate a premium reflecting the option to temporarily close operations. The magnitude of the option premium to close depends on whether firms are out or in the money options.